Smart Backpack Solution for Child Safety Monitoring using GPS Tracker and Internet of Things (IoT) - Puncak Pujiputra, Anggarjuna; Brian, Thomas; Nur Rahayu, Putri; Atmiasri (Universitas PGRI Adi Buana Surabaya, 2025)
Abstract- Supervision of children is an important thing to do for the development of behaviour and child safety. The existence of cases around such as after school not going straight home, skipping school to play online games, even in the mass media there are cases of elementary school children who do not go home immediately. in the mass media there are cases of elementary school children who died from drowning while playing. This can cause parents to worry about their children. On the other hand, the space for parents to supervise children directly is limited due to their activities such as taking care of the house or working, so there is an alternative to make a tracking device or GPS Tracker with the concept of the Internet of Things (IoT) that can solve the problem. The manufacturing method includes three stages, namely the design stage, the testing stage, and data analysis stage in order to produce the expected tool. The results of this research are first, GPS Tracker is built by three main components (Ardunino Nano, Ublox NEO-6M, and SIM800L). Second, the tool functions optimally when outside the room with percentage of error 0% and less than maximum when indoors with an error of 40%. room with 40% error. Third, the device is able to track position at various distances. Fourth, the tool has an average working endurance of 4 hours 26 minutes with a power source of 3.7 VDC 3500mAH battery.